علاقة الإبداع الروائي بتعليمية الأدب الشعبي الجزائري ( روايات "الطاهر وطار" أنموذجا) - مغشيش, عبد المالك (Revues faculté des lettres et des langues; No 13 (2013): مجلة كلية الآداب واللغات)
تعتبر المادة الشعبية بما تحمله من زخم معرفي ثقافي وفني أدبي، أهم رافد يتكئ عليه الخطاب الروائي المعاصر، فباعتباره نتاج بيئة معينة فهو يعكس سياقات فكرية تتنوع بين الفلسفية و الدينية و اللغوية و الأدبية، مما قد يحقق له صيرورة الانفتاح على أزمنة لاحقة تخلقها عقول تعي ضرورة تأصيل الحداثة بالعودة المستلهمة لما صلح من الإبداعات المحلية.ومن هنا يكتسب النص الشعبي صلاحية معينة يتجدد شكلها بتجدد الوعي و الاستخدام أو التوظيف الفعال، فيصبح جاهزا لكل التطورات و الرؤى التي تمتد إليه لتلتقط ما يناسب مذهبها و توجهها المعرفي الفني.   و قد كان الروائي المعاصر أكثر المتعاملين مع الآداب المحلية الشعبية دينامية و تحررا ،يبدو ذلك من خلال نجاحه في ترهين النظر إلى الموروث الشعبي، وإقامة صلاته بالواقع المعيش في مختلف تجلياته ، وتعد هذه الصلة التي حققها المبدع الروائي من العوامل التي تجعل التراث يُبعث من الأحقاب الزمنية التي أنتج فيها ليكون مادة أدبية حيوية تتناقلها الأجيال الأدبية .      The article popular, including in respect of the momentum of cognitive cultural and technical literature, the most important tributary of leaning upon the letter novelist contemporary As number the product of a particular environment, reflects contexts of thought, ranging from the philosophical, religious, and linguistic and literary, which may bring him a process of opening up to the later times created by the minds of aware of the need rooting modernity inspired to return to the reconciliation of the local creations. Hence the validity of the popular text takes a particular form is renewed and renewed awareness of the effective use or employment, it becomes ready for all developments and insights that extend it to pick up the appropriate doctrine and knowledge-oriented artwork.    And has been a novelist of contemporary more dealers with the literature of local dynamic and liberal, it seems that through his success in Mortgage seen Heritage popular, and the establishment of links to reality Living in various manifestations, is the link made by the creative novelist of the factors that make heritage a matter of eras of time that produced the material to be passed between generations vital literary .